A Bibliometric Analysis of Child Language During 1900–2021 - Guo, Xingrong (Frontiers in Psychology, 2022)
This study purpose to provide a bibliometric overview of Child Language (CL) research from 1900 to 2021 and identify major trends in CL. A total of 48,453 research articles related to the CL were identified from the Web of Science. Co-authorship, co-word, and co-citation analysis was conducted by using VOSviewer and CiteSpace. The following was analyzed: annual distribution of related papers; related disciplines; mainstream journals; geographical and institutional distribution; hot topics; keyword burst detection; co-citation analysis of journals, authors, and references. Results showed that under the impact of new empirical methods and new theories, the field of CL is undergoing great changes. Research hotspot and the research trends mainly concentrated on autism spectrum disorder, school readiness, oral language, reading-comprehension, exposure, bilingualism, vocabulary, input, skills, kindergarten, cochlear implants, and intervention. More and more research focus on the individual difference in CL development and the importance of intervention in language education by typically-developing children and some children with disabilities or language disorder. Besides, child second language acquisition also attracted a lot of attention. This bibliometric analysis is of great reference significance for researchers to understand the progress and discipline development trend in this field.